Implementasi Pendekatan Inkuiri dalam Meningkatkan Ketuntasan Belajar pada Mata Pelajaran Matematika Bagi Siswa SMP Negeri 4 Setia Bakti Kabupaten Aceh Jaya - Marwan Marwan (Pencerah, 2022)
This study discusses learning methods in the field of mathematics with an inquiry approach at SMP 4 Setia Bakti, Aceh Jaya Regency. Inquiry aims to see the success of student learning in the field of mathematics in accordance with the planned target. Meanwhile, this research method uses a descriptive approach with data collection techniques through interviews, documentation and observations made to class VIII students of SMP 4 Setia Bakti. The results of the study can be said that the inquiry method in mathematics has an impact on teachers in managing inquiry learning as an effort to achieve mastery learning mathematics for three cycles has increased from cycle I, cycle II, and cycle III with good categories. In addition, during the three cycles of learning in general, there was an increase in terms of: (1) student activities during learning; (2) Classical student learning mastery in the first cycle to the second cycle increased to and slightly decreased in the third cycle but this decrease was not significant because the KKM had been achieved.